Gender, Conflict, and Development - Bouta, Tsjeard; Frerks, Georg; Bannon, Ian (Washington, DC: World Bank, 2013)
This book highlights the gender dimensions of conflict, organized around major relevant themes such as female combatants, sexual violence, formal and informal peace processes, the legal framework, work, the rehabilitation of social services and community-driven development. It analyzes how conflict changes gender roles and the policy options that might be considered to build on positive aspects while minimizing adverse changes. The suggested policy options and approaches aim to take advantage of the opportunity afforded by violent conflict to encourage change and build more inclusive and gender balanced social, economic and political relations in post-conflict societies. The book concludes by identifying some of the remaining challenges and themes that require additional analysis and research.